THE INFLUENCE OF BIOTOPE DENDROFLORA SPECIES COMPOSITION IN THE TOWN OF POLTAVA ON MISTLETOE (VISCUM ALBUM L.) SPREADING - Pischalenko, M. A.; Barabolia, O. V.; Chaika, T. O. (Scientific Progress & Innovations, 2020)
The results of analyzing the influence of biotope dendroflora species composition in the town of Poltava on spreading and the degree of infesting foliage tree species with mistletoe during 2016–2019 in park zones of the town have been presented. While conducting studies, the materials of tour and experimental research-es in Kyivskyi, Podilskyi, and Shevchenkivskyi residential districts of the regional center were used. The conducted studies have shown that negative dynamics has lately been observed as to foliage tree species in-festation with mistletoe (Viscum album L.). Among the investigated districts, green plantings of Shevchen-kivskyi district are infested most of all (25.2 %) and those of Podilskyi district are the least infested (12.1 %). Considerable tree infestation process in street plantings can be explained by high anthropogenic load on them, namely a high degree of technogenic effect, soil pollution with heavy metals, dry city air, and mechan-ical injuries, which in their turn weakens immunity and decreases the resistance of street plantings to pests, diseases, and semi-parasites. One of the main reasons of infesting trees with mistletoe in park plantings is close placing of infested and healthy trees, which is strengthened by considerable anthropogenic pressure and selectivity of the parasite to tree species prevailing in park dendroflora. According to the results of the studies, tree species were determined, which due to their biological-physiological peculiarities are most of-ten infested with mistletoe (Viscum album L.) and those ones, which, on the contrary, are more resistant to the effect of this parasite. The conducted analysis enabled to develop recommendations as to rehabilitation of biotope species composition in Poltava taking into account their resistance to mistletoe infestation de-pending, in particular, on bark structure and thickness. The determining of the most resistant tree species can also be recommended for improving species composition of park zones in urban eco-system as part of measures to clean tree plantings in Poltava. Taking into account the results of the conducted research will enable to develop practical recommendations, aimed at improving the situation as to mistletoe (Viscum album L.) not only in residential districts of Poltava, but also at optimizing green plantings of any populated area.